Collective Action Clauses before they had airplanes: Bondholder committees and the London Stock Exchange in the 19th Century (1827-1868) - Marc Flandreau (Graduate Institute of International and Development Studies, 2013)
This paper unpacks the operation of foreign debt bondholder committees before the creation of the British Corporation of Foreign Bondholders (CFB) in 1868. I argue that many ideas about this period need to be revisited. In particular, my evidence (which uses archival work to describe market microstructures) shows the importance of the London Stock Exchange as a Court of Arbitration. I show how the LSE General Purpose Committee set up a system of Collective Action Clauses, requiring majority agreement among bondholders to sanction a restructuring deal and permit market access. I argue that (unlike what research has argued thus far) this created powerful incentives for bondholders to get organized as they did. Previous models and formal analyses need to be recast. The CFB appears to have been an experiment in statutory restructurings rather than one in coordination.
Keywords: 330